Students’ perception on the use of the Duolingo application as a medium for developing university-level English language skills - Kamsik, Ario Ericsson; Daud, Afrianto; Masyhur, Masyhur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Duolingo has been a popular application for language learning nowadays. Using survey design, this study aims to investigate students' perceptions of the Duolingo app for improving English skills at a university in Indonesia. Over half the students surveyed actively use Duolingo. The findings reveals that 51 of the users poses positive attitudes towards the app. Students found that the app was most useful for enhancing listening and speaking skills, including pronunciation and fluency, due to Duolingo's interactive listening exercises and speech recognition features. Gamification elements like points and badges also made learning more enjoyable and maintained student motivation. These audio-focused, gamified, interactive features are what enabled Duolingo to build university students' oral/aural English skills and communicative competence. Additionally, students appreciated Duolingo’s ability to facilitate mobile learning and simple, self-paced studying.. In summary, findings indicate Duolingo's audio-focused, gamified, interactive features have potential for building university students' oral/aural English skills and communicative competence.